2006
DOI: 10.1021/jm060656o
|View full text |Cite
|
Sign up to set email alerts
|

1-Aminomethylbenzocycloalkanes:  Conformationally Restricted Hallucinogenic Phenethylamine Analogues as Functionally Selective 5-HT2A Receptor Agonists

Abstract: A series of conformationally restricted analogues of the hallucinogenic phenethylamine 1 (2,5-dimethoxy-4-bromophenethylamine, 2C-B) was synthesized to test several hypotheses concerning the bioactive conformation of phenethylamine ligands upon binding to the 5-HT(2A) receptor. These benzocycloalkane analogues were assayed for their receptor binding affinity and ability to activate downstream signaling pathways, and one exceptional compound was selected for testing in an in vivo drug discrimination model of ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
95
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(99 citation statements)
references
References 29 publications
1
95
1
Order By: Relevance
“…An increased expression of KCC2 in the plasma membrane, at least in part, provides the molecular basis of this restoration. (Table S1), to further identify the subtype of 5-HT 2 R that are involved, we used (4-bromo-3,6-dimethoxybenzocyclobuten-1-yl)methylamine hydrobromide (TCB-2), a high-affinity 5-HT 2A R agonist (21,22) (Table S1). TCB-2 at low concentration (0.1 μM; n = 6) hyperpolarized E IPSP by ∼4 mV in control rats ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…An increased expression of KCC2 in the plasma membrane, at least in part, provides the molecular basis of this restoration. (Table S1), to further identify the subtype of 5-HT 2 R that are involved, we used (4-bromo-3,6-dimethoxybenzocyclobuten-1-yl)methylamine hydrobromide (TCB-2), a high-affinity 5-HT 2A R agonist (21,22) (Table S1). TCB-2 at low concentration (0.1 μM; n = 6) hyperpolarized E IPSP by ∼4 mV in control rats ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…80,106 In addition, virtual docking studies allowed the design of new agonist ligands as well as the prediction of their more active enantiomers. 104,105 More recently, Isberg et al 79 have developed an in silico-activated model of the 5-HT 2A receptor starting with the published crystal structure of the β-2-adrenergic receptor. Continued refinements of this, and other G protein coupled receptors, will ultimately allow a greater understanding of the molecular features that lead to receptor binding and activation.…”
Section: Receptor Modelsmentioning
confidence: 99%
“…Contracting the five-membered ring to a cyclobutene, however, gave highly potent 64, (3-bromo-2,5-dimethoxybicyclo[4.2.0]octa-1,3,5-trien-7-yl)methanamine, known as TCB-2. 105 Virtual docking of this molecule to a homology model of the receptor also had predicted that the R enantiomer would be most active. Indeed, pharmacological evaluation revealed that the R benzocyclobutene 64 had a K i of 0.26 nM, while the S isomer had a K i of only 42 nM.…”
mentioning
confidence: 99%
“…The heptahelical serotonin 2A receptor (5-HT2AR) is a GPCR that couples primarily with Gq proteins, yet several cellular studies have shown that this receptor can have different signaling and trafficking profiles depending on the nature of the ligand bound (1,(10)(11)(12)(13)(14)(15). However, such divergences in ligand-directed signaling have yet to be correlated with drug-induced behaviors.…”
mentioning
confidence: 99%